Molecular signatures and phylogenomic analysis of the genus Burkholderia: proposal for division of this genus into the emended genus Burkholderia containing pathogenic organisms and a new genus Paraburkholderia gen. nov. harboring environmental species - Sawana, Amandeep; Adeolu, Mobolaji; Gupta, Radhey S. (Frontiers in Genetics, 2014)
The genus Burkholderia contains large number of diverse species which include many clinically important organisms, phytopathogens, as well as environmental species. However, currently, there is a paucity of biochemical or molecular characteristics which can reliably distinguish different groups of Burkholderia species. We report here the results of detailed phylogenetic and comparative genomic analyses of 45 sequenced species of the genus Burkholderia. In phylogenetic trees based upon concatenated sequences for 21 conserved proteins as well as 16S rRNA gene sequence based trees, members of the genus Burkholderia grouped into two major clades. Within these main clades a number of smaller clades including those corresponding to the clinically important Burkholderia cepacia complex (BCC) and the Burkholderia pseudomallei groups were also clearly distinguished. Our comparative analysis of protein sequences from Burkholderia spp. has identified 42 highly specific molecular markers in the form of conserved sequence indels (CSIs) that are uniquely found in a number of well-defined groups of Burkholderia spp. Six of these CSIs are specific for a group of Burkholderia spp. (referred to as Clade I in this work) which contains all clinically relevant members of the genus (viz. the BCC and the B. pseudomallei group) as well as the phytopathogenic Burkholderia spp. The second main clade (Clade II), which is composed of environmental Burkholderia species, is also distinguished by 2 identified CSIs that are specific for this group. Additionally, our work has also identified multiple CSIs that serve to clearly demarcate a number of smaller groups of Burkholderia spp. including 3 CSIs that are specific for the B. cepacia complex, 4 CSIs that are uniquely found in the B. pseudomallei group, 5 CSIs that are specific for the phytopathogenic Burkholderia spp. and 22 other CSI that distinguish two groups within Clade II. The described molecular markers provide highly specific means for the demarcation of different groups of Burkholderia spp. and they also offer novel and useful targets for the development of diagnostic assays for the clinically important members of the BCC or the pseudomallei groups. Based upon the results of phylogenetic analyses, the identified CSIs and the pathogenicity profile of Burkholderia species, we are proposing a division of the genus Burkholderia into two genera. In this new proposal, the emended genus Burkholderia will correspond to the Clade I and it will contain only the clinically relevant and phytopathogenic Burkholderia species. All other Burkholderia spp., which are primarily environmental, will be transferred to a new genus Paraburkholderia gen. nov.